2013
DOI: 10.1073/pnas.1315320110
|View full text |Cite
|
Sign up to set email alerts
|

Strong cross-system interactions drive the activation of the QseB response regulator in the absence of its cognate sensor

Abstract: Significance Bacteria use regulatory modules called two-component systems to respond to changes in their surrounding environment. Bacteria have evolved ways to insulate each two-component system, thereby preventing unwanted cross-talk. Here we describe an example where partners of distinct two-component systems show remarkable cross-specificity for each other. Loss of the quorum-sensing Escherichia coli (Qse)BC sensor QseC leads to robust cross-interaction of its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
125
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(140 citation statements)
references
References 32 publications
12
125
0
1
Order By: Relevance
“…As expected, the primary phosphodonor for QseB is its cognate sensor, QseC, but interestingly QseB could be partially activated and induce transcription of ygiW-qseBC in the absence of QseC. The absence of QseC in E. coli results in constitutively high qseB transcription that arises from bidirectional crossregulation between the structurally related QseBC and PmrAB two-component systems (Guckes et al, 2013). Without QseC, the non-cognate PmrB kinase phosphorylated QseB and transcription of qseBC was also activated by PmrA resulting in constitutive expression of qseB.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…As expected, the primary phosphodonor for QseB is its cognate sensor, QseC, but interestingly QseB could be partially activated and induce transcription of ygiW-qseBC in the absence of QseC. The absence of QseC in E. coli results in constitutively high qseB transcription that arises from bidirectional crossregulation between the structurally related QseBC and PmrAB two-component systems (Guckes et al, 2013). Without QseC, the non-cognate PmrB kinase phosphorylated QseB and transcription of qseBC was also activated by PmrA resulting in constitutive expression of qseB.…”
Section: Discussionsupporting
confidence: 56%
“…Consistent with latter possibility, the genes that encode enzymes required for the production of acetylphosphate are present in the A. actinomycetemcomitans genome [D11S-1227 (pta) and D11S-1228 (ackA)]. Interestingly, the PmrAB two-component system of E. coli senses ferric iron and induces the expression of qseBC in response to this signal (Chen & Groisman, 2013;Guckes et al, 2013). In contrast, in the absence of PmrAB in A. actinomycetemcomitans, the induction of ygiW-qseBC expression in response to ferrous and ferric iron is dependent on QseBC itself, and appears to be similar to ferrous iron induction of H. influenzae ygiW-fisRS expression (Steele et al, 2012).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Studies in uropathogenic Escherichia coli (UPEC) investigating the basis of bacterial attenuation in the ΔqseC mutant uncovered that loss of QseC leads to a high abundance of phosphorylated response regulator (QseBϳP) that aberrantly regulates metabolic and virulence determinants (12,14). Subsequent studies identified that increased levels of QseBϳP in the qseC deletion mutant were due to the interaction of QseB with the PmrB sensor kinase of the PmrAB TCS (15). In vivo and biochemical studies demonstrated that PmrB could indiscriminately phosphorylate QseB at rates comparable to QseC and that deletion of the pmrB gene in the qseC deletion strain suppressed all the defective phenotypes associated with the absence of QseC (12,(14)(15)(16)(17).…”
mentioning
confidence: 99%
“…103) QseC-QseB senses and binds not only the bacterial hormone-like AI (autoinducer)-3 signal but also the host epineprhine/norepineprhine hormones, 104) thereby inducing the flhDC operons coding for the master regulator of flagella and motility genes.…”
Section: Regulation Network Of the Metal Regulongsmentioning
confidence: 99%